The Negotiations of Services of Health and Education in Argentina: Between Commercial Liberalization and Technical Cooperation - Botto, Mercedes; Peixoto Batista, Juliana (Education Policy Analysis Archives, 2008)
The aim of this article is to analyze the Argentine experience on the commercial negotiations of education and health services. Firstly, we closely examine the negotiations' dynamics of these sectors in diverse forums for negotiation, such as the multilateral, the hemispheric, and the interregional and regional ones. In addition, we determine the advances on the matter, identifying the existence of commercial agendas as well as issues regarding cooperation. The authors emphasize on the existing tension between these two agendas—cooperation and liberalization—, that although antagonizing in the rhetoric, they are reciprocally connected in the facts. Finally, the debate at the national level is analyzed, differentiating the contents and the construction of the argentine negotiating position, where nongovernmental actors have played a preponderant role. The primary data sources come from semi-structured interviews to the argentine delegations that participated in the negotiations during 1992 and 2005, official and negotiating position documents, and technical and research studies of the negotiation process.